1993
DOI: 10.1128/jvi.67.10.6025-6032.1993
|View full text |Cite
|
Sign up to set email alerts
|

Human membrane cofactor protein (CD46) acts as a cellular receptor for measles virus

Abstract: A monoclonal antibody (MCI20.6) which inhibited measles virus (MV) binding to host cells was previously used to characterize a 57to 67-kDa cell surface glycoprotein as a potential MV receptor. In the present work, this glycoprotein (gp57/67) was immunopurified, and N-terminal amino acid sequencing identified it as human membrane cofactor protein (CD46), a member of the regulators of complement activation gene cluster. Transfection of nonpermissive murine cells with a recombinant expression vector containing CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
299
2
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 795 publications
(312 citation statements)
references
References 26 publications
6
299
2
4
Order By: Relevance
“…Another possibility could be the possible usage of other receptors by PPRV. In case of MV, in addition to SLAM or CD150, CD46 has also been shown to play an important role in virus entry (Dorig et al, 1993;Naniche et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility could be the possible usage of other receptors by PPRV. In case of MV, in addition to SLAM or CD150, CD46 has also been shown to play an important role in virus entry (Dorig et al, 1993;Naniche et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The structures of the globular heads of HN proteins display a conserved b-sheet propeller motif, which was identified originally in influenza virus NA, and an SA binding site located in the central cavity of the proteins [39,40]. Unlike HN, the hemagglutinin (H) of measles virus (MV), which also belongs to the Paramyxoviridae family, possesses an inactivated SA receptor binding site and recognizes specific proteins, such as signal lymphocyteactivating molecule (SLAM), CD46, and nectin-4 [41][42][43]. The structure of the globular heads of H protein still reveals a conserved b-sheet propeller motif, and the specific protein receptors bind to the side part of H protein with different orientations [44].…”
Section: Reviewmentioning
confidence: 99%
“…When categorizing morbillivirus attributes it is essential to focus exclusively on wild-type morbillivirus strains as overarching generalizations cannot be made if vaccine viruses and laboratory-adapted strains are included since adaptation during in vitro passage in inappropriate cell lines is common. This is best illustrated by the first, and least clinically-relevant receptor identified for MV, CD46 [1,2] a cell surface molecule used in vitro by laboratory-adapted and vaccine strains but not by wild-type viruses [3]. Immunization of macaques with a recombinant (r) MV derived from the Edmonston-Zagreb (EZ) vaccine strain grown in CD46 expressing MRC-5 cells demonstrated that even though the vaccine virus uses CD46 in vitro this is not the case in vivo [4].…”
Section: What Makes a Morbillivirus?mentioning
confidence: 99%